Effects of hydrogen radical treatment on piezoresistance coefficients of germanium. (1st April 2023) - Matsuda, Kazunori; Yamamoto, Masashi; Mikawa, Michio; Nagaoka, Shiro; Mori, Nobuya; Tsutsui, Kazuo
Abstract: We investigate the effects of hydrogen radical treatment on piezoresistance coefficients of germanium under uniaxial stress up to ±500 μ strain over the temperature range −30 °C to 25 °C. Hydrogen radicals are produced by hydrogen gas (99.99%, 2.7 kPa) on a hot tungsten catalyst (1800 °C). The gauge factor and majority carrier on non-dope germanium dramatically changed from n - to p -type after the hydrogen radical treatment. The results suggest that the piezoresistance coefficients of germanium are seriously affected by vacancy-related levels around the midgap, which behave as donors or acceptors depending on the Fermi level and are passivated by the hydrogen radicals.